Isolation, Molecular Typing, and Antibiotic Susceptibility Testing of Mycobacterium avium Subspecies hominissuis From a Dog With Generalized Mycobacteriosis - Marianelli, Cinzia; Ape, Daniela; Rossi Mori, Federica (Frontiers in Veterinary Science, 2020)
Mycobacterium avium-intracellulare complex infections are becoming an increasing concern in veterinary medicine because they affect livestock, wildlife and companion animals. Here we describe the isolation, molecular typing and antibiotic susceptibility testing of the causative agent of a rare case of generalised mycobacteriosis in a crossbred dog. Mycobacterial colonies were isolated from a popliteal lymph node aspirate sample and molecular typed by SNPs typing of the genes gyrB and rpsA, the 3’ region of the hsp65 gene and the internal transcribed spacer (ITS), and MIRU-VNTR analysis. Colonies were also tested in vitro against the macrolide clarithromycin and other drugs, using a resazurin microdilution assay, in order to provide the most appropriate treatment for the dog. Results from SNPs typing of gyrB and ITS, as well as from MIRU-VNTR analysis suggested the isolation of a single strain of M. avium subsp. hominissuis (Mah). On the other hand, SNP typing of rpsA revealed DNA polymorphisms that led colonies to cluster into two groups. The presence of two distinct strains of Mah has been assumed. All colonies, regardless of the nucleotide sequence of rpsA, were found to be sensitive to all of the drugs tested except for ethambutol. Although the therapy administered was adequate, the dog's overall clinical status worsened progressively and the animal died eight months later. In conclusion, we report on the isolation of Mah from a dog with generalised mycobacteriosis.